International obligations governing the use of transboundary fossil aquifers : a study of customary international law (2019)
In this investigation, I will describe the content and scope of the customary obligations governing the use of transboundary fossil aquifers. I will begin describing these aquifers as one type of shared natural resources that are not thoroughly regulated by treaty law. Then, I will look for evidence of a rule of custom specifically governing these aquifers. Despite that the evidence does not support the existence of such rule, I will argue that States must use these aquifers according to the customary obligations governing the use of all shared natural resources. Lastly, I will describe the content of these obligations.